Nurse managers experiences of their leadership roles in a specific mining primary healthcare service in the West Rand - Sanele E. Nene; Hafisa Ally; Elizabeth Nkosi (AOSIS, 2020)
Background: Nurse managers are leaders in mining primary healthcare. Their leadership roles include inspiring and empowering operational managers and nursing personnel, by leading with competence developing them to become followers with insight and direction. However, these leadership roles are not clearly defined, and are negatively influenced by the traditional mining leadership style. Objectives: The aim of this study was to explore and describe the nurse managers' experiences of their leadership roles in a specific mining primary healthcare service on the West Rand, to develop recommendations to enhance these roles. Method: A qualitative, exploratory, descriptive and contextual research design was used in this study, following a phenomenological approach as a research method. A non-probability purposive sampling method was used. Nurse managers described experiences of their leadership roles during individual phenomenological interviews. Data saturation was reached on participant number 7. To analyse data, four stages of Giorgi's descriptive phenomenological data analysis was used. An independent coder coded the data and a consensus meeting was held. The study was guided by the theoretical framework of Winkler's role theory. Results: The following subthemes emanated from data analysis: (1) leadership role ambiguity, (2) leadership roles experienced and (3) challenges experienced in leadership roles. Conclusion: This study revealed that the leadership roles for nurse managers in a specific mining primary healthcare service are not clearly defined. Hence enhancements and expansions of these leadership roles remained stagnant. A clearly defined policy on leadership roles for nurse managers should be developed.